Burn down, rise up ebook - Tirado, Vincent (2022)
The 2023 Pura Belpré Award-winning young adult novel! Mysterious disappearances. An urban legend rumored to be responsible. And one group of friends determined to save their city at any cost. Stranger Things meets Jordan Peele in this acclaimed novel from an incredible new voice. For over a year, the Bronx has been plagued by sudden disappearances that no one can explain. Sixteen-year-old Raquel does her best to ignore it. After all, the police only look for the white kids. But when her crush Charlize's cousin goes missing, Raquel starts to pay attention—especially when her own mom comes down with a mysterious illness that seems linked to the disappearances. Raquel and Charlize team up to investigate, but they soon discover that everything is tied to a terrifying urban legend called the Echo Game. The game is rumored to trap people in a sinister world underneath the city, and the rules are based on a particularly dark chapter in New York's past. And if the friends want to save their home and everyone they love, they will have to play the game and destroy the evil at its heart—or die trying.